2019
DOI: 10.1002/pola.29356
|View full text |Cite
|
Sign up to set email alerts
|

Modification of proline‐based 2,5‐diketopiperazines by anionic ring‐opening polymerization

Abstract: 2,5-Diketopiperazines (DKPs) are the smallest cyclic dipeptides found in nature with various attractive properties. In this study, we have demonstrated the successful modification of proline-based DKPs using anionic ring-opening polymerization (AROP) as a direct approach. Four different proline-based DKPs with various side chains and increasing steric hindrance were used as initiating species for the polymerization of 1,2-epoxybutane or ethoxyethyl glycidyl ether in the presence of t-BuP 4 phosphazene base. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…mPEG‐ b ‐PEEGE copolymers were synthesized by anionic ring‐opening polymerization using mPEG‐ t BuP 4 as initiating system ( Figure A). mPEG hydroxyl end‐groups were deprotonated by t BuP 4 phosphazene base, generating extremely reactive alcoholates associated with phosphazenium cations, which initiated the polymerization of EEGE monomers . Molar masses determined by size exclusion chromatography and 1 H NMR are in good agreement with the theoretical ones ( Table 2 ).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…mPEG‐ b ‐PEEGE copolymers were synthesized by anionic ring‐opening polymerization using mPEG‐ t BuP 4 as initiating system ( Figure A). mPEG hydroxyl end‐groups were deprotonated by t BuP 4 phosphazene base, generating extremely reactive alcoholates associated with phosphazenium cations, which initiated the polymerization of EEGE monomers . Molar masses determined by size exclusion chromatography and 1 H NMR are in good agreement with the theoretical ones ( Table 2 ).…”
Section: Resultssupporting
confidence: 70%
“…mPEG hydroxyl end-groups were deprotonated by tBuP 4 phosphazene base, [47] generating extremely reactive alcoholates associated with phosphazenium cations, which initiated the polymerization of EEGE monomers. [48,49] Molar masses determined by size exclusion chromatography and 1 H NMR are in good agreement with the theoretical ones ( Table 2). The polymerization degree of the hydrophobic EEGE block is defined by the [M] 0 /[I] 0 ratio, allowing the control of the copolymer hydrophilic-hydrophobic balance.…”
Section: Synthesis and Characterization Of Copolymerssupporting
confidence: 81%
“…We also observed that in that polymerization system, coinitiation from residual water was sometimes unavoidable, even by working with utmost care . This undesired initiation has been frequently found in polymerization systems catalyzed by t -BuP 4 . , …”
Section: Introductionmentioning
confidence: 59%
“…hydrogen and a conjugated carbonyl moiety, which were likely to react with the anionic propagating centers. [31][32][33] However, no interferences with the mechanism of the alternating polymerization have been evidenced. With the help of a 1 H- 15 N heteronuclear single quantum correlation (HSQC) NMR spectrum, the large 1 H NMR signal between 6.8 and 7.6 ppm could be attributed to NH of the unmodified acetamido groups (Figure 2).…”
Section: ð (Sec) [°C] [H] [%] [G Molmentioning
confidence: 99%
“…It was previously demonstrated that higher amount of phosphazene base favor the occurrence of side-reaction due to an increase the propagating center reactivities. [32][33] A polymerization in the bulk at 90°C resulted in high dispersity polymer (Table 1, run 6). In order to increase the M n , a reaction was performed at 60°C by increasing the ([NHTL] 0 +[tBuGE] 0 )/[ROH] 0 ratio (Table 1 run 9, X n,targeted = 80).…”
Section: ð (Sec) [°C] [H] [%] [G Molmentioning
confidence: 99%